High-yielding nanobelt formation by chirality-assisted synthesis - Singh, Yogendra; Schuldt, Moritz P.; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2025)
Shape-persistent conjugated nanobelts (CNBs) are fascinating synthetic targets. However, in most cases these are made in low overall yields by applying strategies of macrocyclization followed by (multiple) ring fusion reactions for nanobelt formation. Here, we describe the high yielding synthesis of enantiopure chiral nanobelts in 84 % yield by applying chirality-assisted synthesis (CAS). The chiral nanobelts were investigated by UV/Vis and CD spectroscopy. By DFT calculations the aromaticity of these structures is discussed.
Online verfügbar: 14. Oktober 2024
Gesehen am 12.05.2025